Self-assembled lipid-based nanoparticles for chemotherapy against breast cancer - Liu, Shan (Frontiers in Bioengineering and Biotechnology, 2024)
Self-assembled lipid-based nanoparticles have increased therapeutic efficacy and reduced toxic side effects. Breast cancer is a common malignant tumor among women. Conventional drugs such as doxorubicin (DOX) show low therapeutic efficacy and high drug toxicity in antitumor therapy. This paper survey the research of the self-assembled lipid-based nanoparticles, categorizing them into three groups: self-assembled liposomal nanostructures, self-assembled niosomes, and self-assembled lipid polymer-hybrid nanoparticles. Subsequently, the structural features, operational mechanisms of each group are individually summarized. Also, the representative drugs of each group are exhibited.